2009
DOI: 10.1002/cmmi.289
|View full text |Cite
|
Sign up to set email alerts
|

Ferumoxides–protamine sulfate is more effective than ferucarbotran for cell labeling: implications for clinically applicable cell tracking using MRI

Abstract: The use of superparamagnetic iron oxide (SPIO) for labeling cells holds great promise for clinically applicable cell tracking using magnetic resonance imaging. For clinical application, an effectively and specifically labeled cell preparation is highly desired (i.e. a large amount of intracellular iron and a negligible amount of extracellular iron). In this study we performed a direct comparison of two SPIO labeling strategies that have both been reported as efficient and clinically translatable approaches. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…It was suggested that the additional carboxyl groups associated with ferucarbotran might lead to a higher affinity to the cell membrane so that cells could be labeled with it without need of an incorporation facilitator [48,49]. However, recent work showed that a higher percentage of labeled cells, a higher amount of intracellular iron and lower amount of extracellular iron aggregates were reached using FeProt complexes when compared to Resovist without incorporation facilitator [33]. Moreover, in a study on human MSC (hMSC), there was no difference in the total iron content (pg/cell) among cells incubated with Feridex or Resovist when both were added together with PLL; both Feridex and Resovist incorporation was superior to a third type of nanoparticle [monocrystalline iron oxide (MION), an ultrasmall superparamagnetic iron oxide] when added with PLL [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that the additional carboxyl groups associated with ferucarbotran might lead to a higher affinity to the cell membrane so that cells could be labeled with it without need of an incorporation facilitator [48,49]. However, recent work showed that a higher percentage of labeled cells, a higher amount of intracellular iron and lower amount of extracellular iron aggregates were reached using FeProt complexes when compared to Resovist without incorporation facilitator [33]. Moreover, in a study on human MSC (hMSC), there was no difference in the total iron content (pg/cell) among cells incubated with Feridex or Resovist when both were added together with PLL; both Feridex and Resovist incorporation was superior to a third type of nanoparticle [monocrystalline iron oxide (MION), an ultrasmall superparamagnetic iron oxide] when added with PLL [58].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, dextran-coated SPIONs do not show sufficient cellular uptake to enable tracking of nonphagocytic cells [29]. However, the cellular uptake of SPIONs by nonphagocytic cells can be facilitated by cationic compounds such as poly-L-lysine (PLL) [29,30] and protamine sulfate [31-33] due to their interaction with the negatively charged cell surface and subsequent endosomal uptake [29,34]. PLL is a synthetic cationic polymer commonly used to enhance cell adhesion to the surface of culture dishes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the original concentration of applied cells is known in an ACI procedure, and seeded in a confined volume, it is possible to quantify the total amount of labeled cells and follow them in the same patient in subsequent MRI sessions. Since both hBMSCs and chondrocytes can be labeled using SPIO [25], [26], these findings indicate the potential of SPIO labeling for tracking cells in numerous orthopedic treatments and many other regenerative medicine fields [27]. Cell visualization and especially quantification using MRI can be a major step towards improvement in all these applications.…”
Section: Discussionmentioning
confidence: 98%
“…SPIO labeling was performed using ferumoxides (Endorem®, Guerbet S.A., Paris, France) complexed to protamine sulfate (LEO Pharma N.V., Wilrijk, Belgium) as described earlier [25]. For removal of extracellular iron, cells were washed with PBS containing heparin 10 U/ml (LEO Pharma B.V., Breda, the Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…106 The authors and the use of "physicochemical labels" such as magnetic nanoparticles. 110,111 An important advantage of magnetic nanoparticles like "superparamagnetic iron oxide"-labeling over other labeling techniques is that it enables clinical noninvasive in vivo cell tracking using MRI, without the need for harvesting biopsies. This allows for continuous follow-up of biological repair of articular cartilage without influencing the repair tissue or jeopardizing the patient with repeated interventions.…”
Section: Mscs For Cartilage Repairmentioning
confidence: 99%